Exploring C++20 : the programmer's introduction to C++ - Lischner, Ray, 1961- (ITpro collection, 2020)
Discover everything you need to know about C++ in a logical progression of small lessons that you can work through as quickly or as slowly as you need. This book divides C++ up into bite-sized chunks that will help you learn the language one step at a time. Fully updated to include C++20, it assumes no familiarity with C++ or any other C-based language. "Exploring C++20" acknowledges that C++ can be a complicated language, so rather than baffle you with complex chapters explaining functions, classes, and statements in isolation you'll focus on how to achieve results. By learning a little bit of this and a little of that you'll soon have amassed enough knowledge to be writing non-trivial programs and will have built a solid foundation of experience that puts those previously baffling concepts into context. In this fully-revised third edition of "Exploring C++", you'll learn how to use the standard library early in the book. Next, you'll work with operators, objects, and data-sources in increasingly realistic situations. Finally, you'll start putting the pieces together to create sophisticated programs of your own design confident that you've built a firm base of experience from which to grow